Territorial Cohesion and the Pandemic in Romania - Iordan, Marioara; Ghizdeanu, Ion; Braica, Alexandra Patricia (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2021)
Convergence and economic and social cohesion remain priorities for the EU, beyond failures to achieve the objectives of the 'Europe 2020' strategy. Convergence and territorial cohesion, as a prerequisite for sustainable and durable development, have been the fundamental objectives that generated and developed the strategic planning in the EU, including through the two global strategies, 'Lisbon' and 'Europe 2020'. The sustainability of these processes, even in periods of high economic growth, is questionable since real national convergence is based in many countries, including Romania, on large and widening divergences between regions and counties. In recent years, Romania has seen one of the most enhanced improvements in convergence compared to the EU average, from 60% in 2016 to 69% of the European average in 2019 respectively. During the same period, disparities between regions and counties have deepened. More than 10 years after EU accession and participation in the Community cohesion policy, there is still a third of the counties with less than 70% of the national average of gross domestic product per capita. The health crisis has deeply affected economic activity, but in a differentiated way, depending on the specific territorial economic structures. As a result, the objective of improved and sustainable real convergence, by bringing regions and counties closer together in terms of their level of development, is receding. The economic situation in the counties in 2020 indirectly provides support for assessing the impact of the pandemic on the territorial cohesion process. The implicit conclusion revealed by the latest statistical data is that the level of development has been the support for better resilience to the health crisis. Although the restrictions on international movement and the closure of tourist and industrial capacities have had general validity, the counties with a higher degree of disparity have been more affected.